The inclusion engineer with STEAM in the educational institution - Cabrera Medina, Jaime Malqui; Sánchez Medina, Irlesa Indira; Céspedes Muñoz, Boris Alberto (Ingeniería Solidaria, 2022)
Introduction: This article is the product of research carried out in an educational institution in the city of Neiva, where young researchers, in their role as inclusion engineers within higher education, work on video game de-sign through Kodu, during the years 2017 to 2019, in a teaching-learning process of Mathematics and Natural Sciences in primary school with the STEAM methodology.Objective: Strengthen skills in mathematical logic, creativity and environment as a basis for future engineering in fifth grade students. Methodology: The research was of a mixed type, using a documentary analysis for performance levels in ma-thematics and natural sciences in fifth grade, an observation protocol for the characterization of the population, and a verification test in the creation of video games. Results: As part of the statistical analysis, significant progress is evidenced in the results obtained during the three years, and in conclusion, it is considered that the STEAM methodology is adequate to work with Kodu as the appropriate programming environment for the development of competence through video game design in the educational process. Conclusion: The young researchers assume the role of inclusion engineer, using the Kodu programming environment with a STEAM learning methodology that integrates Science, Technology, Engineering, Art and Mathematics through the creation of their own video games, with representative bases to start in the world of engineering.